Development of advanced hydrogenation processes for silicon solar cells via an improved understanding of the behaviour of hydrogen in silicon. (10th January 2020) - Hallam, Brett J.; Hamer, Phill G.; Ciesla née Wenham, Alison M.; Chan, Catherine E.; Vicari Stefani, Bruno; Wenham, Stuart
Abstract: The understanding and development of advanced hydrogenation processes for silicon solar cells are presented. Hydrogen passivation is incorporated into virtually all silicon solar cells, yet the properties of hydrogen in silicon are still poorly understood. This is largely due to the complex behaviour of hydrogen in silicon and its ability to exist in many different forms in the lattice. For commercial solar cells, hydrogen is introduced into the device through the deposition of hydrogen‐containing dielectric layers and the subsequent metallisation firing process. This process can readily passivate structural defects such as grain boundaries but is ineffective at passivating numerous defects in silicon solar cells such as the boron‐oxygen complex, responsible for light‐induced degradation in p‐type Czochralski silicon. This difficulty is due to the need to first form the boron‐oxygen defect and also due to atomic hydrogen naturally occupying low‐mobility and low‐reactivity charge states. However, these challenges can be overcome using advanced hydrogenation processes incorporating excess carrier generation from illumination or current injection that increase the concentration of the highly mobile and reactive neutral charge state. As a result, after fast firing, additional low‐temperature advanced hydrogenation processes incorporating illumination can be implemented to enable the passivation of difficult defects like the boron‐oxygen complex. With the implementation of such processes for industrial silicon solar cells, efficiency improvements of 1.1% absolute can be obtained. Abstract : We present an understanding of hydrogen and the development of advanced hydrogenation processes for silicon solar cells, pioneered by the late Professor Stuart Wenham. Contradictions in the literature related to hydrogen can largely be explained by hydrogen's ability to assume different charge states. Advanced hydrogenation processes incorporating minority carrier injection can greatly enhance the concentration of the highly mobile neutral charge state to enable efficiency enhancements of 1.1% absolute for industrial silicon solar cells.